Efektivitas Media Pembelajaran Cue Card untuk Meningkatkan Hasil Belajar Peserta Didik dalam Pembelajaran Teks Prosedur Kelas VII SMP Negeri 2 Indramayu - Feby HamzahFansyuri; Embang Logita; Saroni Saroni; Rochman Rochman (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2025)
This study aims to examine the effectiveness of cue card media in improving learning outcomes on procedural text material in Grade VII at SMPN 2 Indramayu. Using a quantitative approach with a One-Group Pretest-Posttest design, the study involved 25 students. Data were collected through observation, tests, and documentation. The results showed an increase in learning mastery from 60% to 92% after the use of cue cards. This media effectively enhanced students' understanding of text structure, encouraged active participation, and created an engaging learning atmosphere. Cue cards can be considered an effective alternative media for teaching Indonesian, particularly procedural texts.